Physician snapshot: the forming landscape of MAiD in northwestern Ontario - Durant, Keri-Lyn (Palliat Care Soc Pract, 2020)
BACKGROUND: Options available to Canadians at the end of life increased with the legalization of medical assistance in dying (MAiD). Bill C-14 modified the Canadian Criminal Code allowing individuals who meet very specific criteria to receive a medical intervention to hasten their death. June 2019 marked 3 years since the legislation has changed and while met with favour from most Canadians who believe it will provide enhanced options for quality of life at the end of life, there remains much debate over both its moral implications and practical components. Little is known regarding the Canadian healthcare provider experience with MAiD, in particular in rural and remote parts of the country such as northwestern Ontario. OBJECTIVES: The purpose of this study was to explore physicians’ experiences in Northwestern Ontario with MAiD. The geographic location of this study is of particular significance as physicians in rural and remote parts of Canada face unique challenges in the provision of high-quality palliative and end-of-life services. This qualitative research focused on developing a better understanding of physicians’ perceptions and practices with MAiD, in particular regarding access, decision-making, provision of service and role clarity. METHODS: The researchers employed an exploratory qualitative research approach, using 1 semi-structured focus group and 18 semi-structured interviews comprising 9 set of questions. Data were collected through audio-taped semi-structured interviews, in person and by telephone. FINDINGS: Four distinct but interconnected themes emerged from thematic analysis of the transcripts of the focus group and interviews: physician perception of patient awareness, appreciation and understanding of MAiD; challenges providing true choice at end of life; burgeoning relationships between palliative care and MAiD; and physician recommendations. CONCLUSION: The results of this study provide a snapshot of the Northwestern physician experiences with MAiD and contribute to the growing body of work exploring these issues on a national scale. MAiD is highlighted as both a rewarding and challenging experience for physicians in Northwestern Ontario in this study.